Pengaruh Kualitas Pelayanan Internet Kampus Dan Penugasan Dosen Terhadap Minat Belajar Mahasiswa Program Studi Pendidikan Akuntansi Angkatan 2012 FKIP Universitas Muhammadiyah SurakartaTahun 2014/2015 - Ferdiyanti, Rizky, Dr. Sabar Narimo, MM, M.Pd (2015)
The purpose of this study was to determine: 1) To know impact of service quality on the Internet campus interest in learning. 2) To determine the effect of the interest in learning faculty assignment. 3) To know influence the quality of internet services to the campus and faculty assignments interest This belajar.Penelitian including quantitative research associative with withdrawal conclusions through statistical analysis. The population in this study were students 2012. The accounting education forces the sample is taken as 97 students with simple random sampling. The necessary data obtained through questionnaires and documentation. Questionnaire previously tested and tested for validity and tested reliability. Data analysis technique used is linear regression analysis multiple, F test, t test, and the relative contribution and efektif.Hasil regression analysis obtain a regression line equation: Y = 7.054 + 0, 334 X1 + 0, 622X2. Equation shows that the interest in learning is influenced by the quality of internet services campus and faculty assignment. The conclusions drawn are: 1) Quality Internet service campus positive and significant impact on interest in learning progdi FKIP Muhammadiyah University of Surakarta. Based on t test was obtained thitung> ttable, namely 2.143> 2.000 and the probability value <0.05, namely 0.035. 2) Assignment lecturer positive and significant impact on interest in learning progdi FKIP Muhammadiyah University of Surakarta. Based on t test obtained t> ttable, namely 5.719> 2.000 and the probability value <0.05, namely 0.000. 3) Quality Internet service campus and faculty assignments together against interest in learning progdi FKIP Muhammadiyah University Surakarta.Berdasarkan results multiple linear regression significance test (test F) are known Fhitung> Ftable, ie 176.139> 3.150 and the significance value <0.05, namely 0.000. 4) Variable quality of service campus internet contributed 18% effective. Variable assignment of lecturers contribute effectively 51.4%. so that the total effective contribution both variable by 69.4%, while 30.6% is influenced by other variables is not examined. Keywords: campus internet service quality, faculty assignment, and interest in learning.